2018
DOI: 10.1016/j.actamat.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier transport across grain boundaries in graphene

Abstract: We evaluate the charge carrier transmission across asymmetric grain boundaries (GB) in a graphene lattice within the Landauer-Büttiker formalism. We employ a tight-binding model for C-based materials that accounts for lattice strain introduced by topological defects, such as grain boundaries. In particular, we investigate electronic transmission across grain boundaries found to be stable up to high temperatures. Our calculations suggest that the introduction of GBs generally preserves the zero-transport gap pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Another factor increasing the triboelectric response in the PS-TENG made with 40 mg/mL PS solution is its higher amorphous nature in comparison to other films with higher concentrations, as reported earlier in many studies. The higher amorphous content may promote deep charge trapping in polymeric insulators with aromatic rings in their monomeric structures. Because of the inherent electrical resistivity of polymer films, charges remain largely trapped, which can increase the charge storage capacity of the polymer material. In addition, not only the charge generation but also the surface charge distribution is improved in amorphous films in comparison to crystalline films as a result of lesser grain boundaries, , which may further support higher surface charge density. The transferred charges have been calculated from the integration of the current signal over time (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor increasing the triboelectric response in the PS-TENG made with 40 mg/mL PS solution is its higher amorphous nature in comparison to other films with higher concentrations, as reported earlier in many studies. The higher amorphous content may promote deep charge trapping in polymeric insulators with aromatic rings in their monomeric structures. Because of the inherent electrical resistivity of polymer films, charges remain largely trapped, which can increase the charge storage capacity of the polymer material. In addition, not only the charge generation but also the surface charge distribution is improved in amorphous films in comparison to crystalline films as a result of lesser grain boundaries, , which may further support higher surface charge density. The transferred charges have been calculated from the integration of the current signal over time (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…55−59 Because of the inherent electrical resistivity of polymer films, charges remain largely trapped, which can increase the charge storage capacity of the polymer material. In addition, not only the charge generation but also the surface charge distribution is improved in amorphous films in comparison to crystalline films as a result of lesser grain boundaries, 60,61 which may further support higher surface charge density. The transferred charges have been calculated from the integration of the current signal over time (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Fully coupled thermomechanical-electronic structure calculations of defects in monolayer graphene, including grain boundaries, have been presented in previous work [19]. As noted by numerous authors, the presence of lattice defects profoundly influences the electronic transport properties of graphene, including its band gap structure.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Xiao et al [16] studied the deterioration of the mechanical properties of graphene due to the presence of this type of defects by using an atomistic based finite bond element model. It is found that the Stone-Wales defect modifies the chemical [17] and electronic [18,19] properties of pristine graphene lattices. 7-5 pair structures can also combine to form dislocation dipoles [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high surface to volume ratio of carbon materials causing relatively high specific charge storage, they can be used as an electrode in the energy storage devices such as Supercapacitors. Ideally, a monolayer of sp 2 bonded carbon atoms can reach specific capacitance up to ~550 F/g, large sur-face area of 2675 m 2 /g, high intrinsic mobility of 200,000 cm 2/ (V.s), and optical transmittance around 97.7% (6,(21)(22)(23)(24)(25) , which basically set the upper limit for all carbon materials. Therefore, an extensive attention is given to utilizing graphene in the supercapacitor device (2,(26)(27)(28)(29)(30)(31)(32).…”
Section: Introducctionmentioning
confidence: 99%